Depression, Anxiety and Anger in Adults Who Suffered Myocardial Infarction: A Case- Control Study - García-Batista, Zoilo Emilio (2020)
Cardiovascular Diseases (CVD) are one of the main causes of mortality worldwide. Several studies have proposed that psychological factors explain the morbidity and mortality of CVD, both at the primary and secondary levels. The main objective of the present investigation was to verify the levels of depression, anxiety and anger in people who have suffered a myocardial infarction. Using a case-control design, two groups were contrasted, a group consisting of people who had suffered a myocardial infarction (CVD, n = 33), and another group that served as a control matched by age and sex (n = 33). Although all the contrasted variables present higher levels in the CVD group, only depression presents a statistically significant difference.